Risk Factors for Chronic Malnutrition in Children Aged 6 to 23 Months in BOPA, Southwest Benin (Global Journal of Medical Research, 2023)
During the first two years of a child s life nutritional status is crucial for his or her well-being and growth This study explains the risk factors of chronic malnutrition during the first two years of life in south west Benin The methodological approach uses the construction of Food Consumption Score FCS Reduced Coping Strategies Index rCSI Household Dietary Diversity Score HDDS and Livelihood Coping Strategies LCS The Chi2 test helps to examine the dependency between the variables The simple binary logit model is used to explore the effects of the explanatory variables on the dependent variable The results show that about 27 of children aged 6-23 months are chronically malnourished The age range of the child the type of union the average monthly income of the head of the household the food consumption score and the size of the family determine the chronic malnutrition During difficult times households rely on atypical coping strategy mechanisms by disposing of their productive assets 20 3 of households can marginally cover their minimum food needs using crisis or emergency coping strategy mechanisms
Keywords: Stunting; Benin; Nutrition; Diet; Risk factors